Gradual recovery in Euroland - Kai Carstensen; Klaus-Jürgen Gern; Christophe Kamps; Joachim Scheide (Institut für Weltwirtschaft (IfW), 2003)
The economic situation in the euro area continues to be weak. In the course of 2003, real GDP has only stagnated. Several factors prevented the expected recovery to materialize. Last year's collapse of stock prices dampened activity, so did the high oil price. In addition, the uncertainty in the wake of the conflict with Iraq had a negative impact on the business sentiment and on consumer confidence. Finally, exports were hit by the strong appreciation of the euro. Since the spring of 2003, leading indicators have improved somewhat, but they do not suggest that economic activity will pick up strongly in the second half of this year. All in all, real GDP growth will amount to just 0.5 percent in 2003 and, thus, remain below the trend rate for the third year in a row. In the course of next year, economic activity will accelerate gradually; beginning in the spring, overall capacity utilization will increase again for the first time in three years. One factor supporting the recovery will be exports as growth in the world economy will gain momentum and the dampening factors of the euro appreciation will phase out. Internal demand will be stimulated by low interest rates; investment of firms will pick up, and also consumers will become more optimistic as the labor market situation will slowly improve. For the year as a whole, we expect real GDP to rise by 1.9 percent. Consumer price inflation will remain moderate and be in line with the target of the ECB. The European Central Bank (ECB) will leave key interest rates at their low levels for the time being. If the economy starts to recover in the fourth quarter of this year, as we expect, there will be no reason to loosen the policy stance further. The ECB will most likely start to tighten policy when the upswing has gained momentum and capacity utilization has increased considerably. Therefore, it is not likely that interest rates will already be raised next year. The budget deficits in most countries will again be higher than anticipated in the national Stability Programs. For the year as a whole, the aggregated deficit in the euro area will rise to 2.6 percent in relation to GDP, compared to 2.2 percent last year. Next year, the stance of fiscal policy will be roughly neutral with differences among the member states. The budget situation in Germany is a major cause for concern. Already last year, the deficit exceeded the 3 percent limit of the Stability and Growth Pact (SGP). The same will be true for this year. The current plans for 2004 make it very likely that the deficit will exceed the 3 percent margin once again. A similar scenario can be expected for France, where the announced measures will not prevent the deficit to reach more than 3 percent for the third year in a row. Several governments are acting against their own announcements by allowing excessive deficits to persist. That is in clear contradiction to the Broad Economic Policy Guidelines (BEPG), which call for a continuous reduction of structural deficits. By violating these rules and also the commitments made in the context of the Stability Programs, fiscal policy is losing credibility. Should the Stability Pact fail, it would not be because of its “tight rules” but because governments fail to comply with the rules which they have established themselves
Keywords: 330; Konjunktur; Konjunkturprognose; Europäische Wirtschafts- und Währungsunion; EU-Staaten